El teatro, una actividad artística en el ámbito educativo - Pardo Saavedra, Nelly Andrea (Universidad Pedagógica y Tecnológica de Colombia, 2020)
At the Sugamuxi School, Central headquarters in Sogamoso city, an artistic project is developed with the students of the children’s theater group, in the after- noons of school days. The objective of the following article is to reflect on the importance of theater within the educational environment. The content is part of the work in the direction of the children’s theater group, whose intention seeks to strengthen the communicative and social capacities of the participating children as they are recognized as members of a community.